Ductile damage mechanism under shear-dominated loading: In-situ tomography experiments on dual phase steel and localization analysis. (October 2018) - Roth, Christian C.; Morgeneyer, Thilo F.; Cheng, Yin; Helfen, Lukas; Mohr, Dirk
Abstract: The nucleation, evolution and coalescence of voids is the well-established mechanism leading to ductile fracture under tension-dominated loading conditions. From a theoretical point of view, the same mechanism also applies to shear-dominated loading conditions. Here, an attempt is made to provide for the first time tomographic evidence of damage nucleation and evolution under shear-dominated loading in a modern engineering material. Monotonic experiments are performed on a flat double gage section smiley-shear specimen on the laminography stage of a synchrotron X-ray line. Based on fifteen scans of the entire gage section μm 3, the mesostructural evolution inside a ferrite-bainite steel (FB600) is imaged in 3D up to the instant of specimen fracture. It is found that the as-received material includes a volume fraction of about 0.015% CaO particles. Upon mechanical loading at stress triaxialities evolving from 0 to 0.3, the ductile matrix detaches from these second phase particles, creating a prolate void space whose principal axis is aligned with the principal direction of the applied macroscopic field of deformation. The void space continues to grow while developing micro-crack like features. A large deformation analysis is performed on a representative volume element of the particle-matrix mesostructure replicating the experimental observations of void growth in an approximate manner. Furthermore, the simulation results suggest that a porosity as low as 0.05% is already sufficient to cause the ductile failure under shear-dominated loading through the formation of a band of localized plastic deformation at the mesoscale. Highlights: Determined stress-state dependent fracture initiation in a ferritic-bainitic steel with CaO particles. Performed in-situ shear experiment on synchrotron X-ray line. Observed void nucleation and growth under shear-dominant loading conditions. Explained observed failure mechanism through computational shear localization analysis.